2005
DOI: 10.1007/s00421-005-0095-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-exercise leg and forearm flexor muscle cooling in humans attenuates endurance and resistance training effects on muscle performance and on circulatory adaptation

Abstract: The influence of regular post-exercise cold application to exercised muscles trained by ergometer cycling (leg muscles) or handgrip exercise using a weight-loaded handgrip ergometer (forearm flexor muscles) was studied in human volunteers. Muscle loads were applied during exercise programs three to four times a week for 4-6 weeks. Besides measuring parameters characterizing muscle performance, femoral and brachial artery diameters were determined ultrasonographically. Training effects were identified by compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
121
4
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(131 citation statements)
references
References 35 publications
3
121
4
3
Order By: Relevance
“…This is indeed unusual, as PGC-1α has been well shown to increase NRF1 expression and transcriptional activity (Wu et al, 1999) and consequently suggests other pathways besides PGC-1α might regulate NRF1 expression following post-exercise cold exposure. Regardless, this study lends some support for the study by Yamane et al (2006), as NRF1 has shown to encode a variety of mitochondrial components (Scarpulla, 2002) and PGC-1α has shown to act through ERRα in inducing VEGF expression (Chinsomboon et al, 2009). A key consideration however, that must be accounted for is that the increase in PGC-1α following cold exposure as demonstrated by Slivka et al (2013; was accompanied by significant elevations in whole body VO2 and shivering thermogenesis, which independently may increase PGC-1α mRNA expression.…”
Section: Post-exercise Cold Exposuresupporting
confidence: 60%
See 4 more Smart Citations
“…This is indeed unusual, as PGC-1α has been well shown to increase NRF1 expression and transcriptional activity (Wu et al, 1999) and consequently suggests other pathways besides PGC-1α might regulate NRF1 expression following post-exercise cold exposure. Regardless, this study lends some support for the study by Yamane et al (2006), as NRF1 has shown to encode a variety of mitochondrial components (Scarpulla, 2002) and PGC-1α has shown to act through ERRα in inducing VEGF expression (Chinsomboon et al, 2009). A key consideration however, that must be accounted for is that the increase in PGC-1α following cold exposure as demonstrated by Slivka et al (2013; was accompanied by significant elevations in whole body VO2 and shivering thermogenesis, which independently may increase PGC-1α mRNA expression.…”
Section: Post-exercise Cold Exposuresupporting
confidence: 60%
“…As opposed to passive cold exposure, more studies have investigated the effects of cold exposure following exercise instead Ihsan et al, 2014;Slivka et al, 2013;Slivka et al, 2012;Yamane et al, 2006). In an early study, it was shown that improvements in VO2max and cycling time to exhaustion during single leg cycling following 4 weeks of endurance training were attenuated in the leg subjected to regular post-exercise cooling (2 x 20 min at 5°C) (Yamane et al, 2006).…”
Section: Post-exercise Cold Exposurementioning
confidence: 99%
See 3 more Smart Citations